Development of artificial neural network model for prediction of post-streptococcus mutans in dental caries. (April 2020) - Javed, Syed; Zakirulla, M.; Baig, Rahmath Ulla; Asif, S.M.; Meer, Allah Baksh
Highlights: Pre and post Streptococcus mutans are clinically registered from 45 children with occlusal caries. ANN model was design with trainlm to predict the post Streptococcus mutans . Based on the ANN model built, iOS App is developed; can be installed from Apple App stores. Global clinician can predict the post streptococcus mutans beforehand to excavation using App at ease with no knowledge of ANN. Abstract: Background and objective: Streptococcus mutans is the primary initiator and most common organism associated with dental caries. Prediction of post- Streptococcus mutans favours in the selection of appropriate caries excavation method which eventually results in meliorate caries-free cavity preparation for restoration. The objective of this study is to predict the post- Streptococcus mutans prior to dental caries excavation based on pre- Streptococcus mutans using iOS App developed on Artificial Neural Network (ANN) model. Methods: For the current research work, children with occlusal dentinal caries lesion were chosen, 45 primary molar teeth cases were studied. Caries excavation was done with carbide bur, polymer bur and spoon excavator. The colony forming units for pre and post- Streptococcus mutans were recorded, data emanating from clinical trials was employed to develop the ANN models. ANN models were trained, validated and tested with the registered clinical data using different ANN architectures. Results: Feedforward backpropagation ANN model with an architecture of 4-5-1, predicts post- Streptococcus mutans with an efficiency of 0.99033, mean squared error and mean absolute percentage error for testing cases were 0.2341 and 4.967 respectively. Conclusions: Caries excavation methods and pre- Streptococcus mutans are feed as inputs, while post- Streptococcus mutans as targets to develop ANN model. Based on the developed ANN model, an ingenious iOS App was developed, the global clinician may utilize the App to meticulously predict post- Streptococcus mutans on iPhone based on pre- Streptococcus mutans, which in turn aids in decision making for the selection of caries excavation method. This study manifests the potential application of iOS App with built-in ANN model in efficiently predicting the post- Streptococcus mutans . Also, the study extends scope for applications of iOS App with built-in ANN models in clinical medicine. Graphical abstract: Image, graphical abstract